Optimization of fluxes for Yb3+:YMgB5O10 crystal growth and intense multi-wavelength emission characteristics in spectra and laser performances. Issue 41 (11th October 2021) - Sun, Shijia; Li, Bingxuan; Lou, Fei; Shi, Xingjun; Chen, Weidong; Yuan, Feifei; Zhang, Lizhen; Lin, Zhoubin; Zhong, Degao; Huang, Yisheng; Teng, Bing
Abstract : Yb:YMB crystals were grown using the optimized Li2 O–B2 O3 –LiF flux instead of the traditional K2 O3 –MoO3 flux by the TSSG method. The demonstration of dual-wavelength laser operation reveals the potential in THz generation. Abstract : Yb 3+ -doped YMgB5 O10 (Yb:YMB) crystals with better crystalline quality were grown successfully using the optimized flux of Li2 O–B2 O3 –LiF instead of the traditional K2 O3 –MoO3 flux by the top-seeded solution growth method. The systematic investigation of the crystal growth, structure characteristics, polarized absorption and emission spectra, fluorescence decay curve and laser properties of the Yb:YMB crystal was reported for the first time. The main spectroscopic and laser parameters, such as the absorption coefficients and cross-sections, energy level schema and barycenter plot, radiative and fluorescence lifetime, emission and gain cross-sections, minimum inversion fraction, pump saturation intensity and minimum absorbed pump intensity, have been calculated and analysed in detail. The broad absorption band (FWHM, 18.4 nm, E // Z ) at around 936 nm matches very well with the emission wavelength of InGaAs laser diodes. The intense spectra anisotropy and multi-wavelength emission characteristics make it possible to realize the multi-wavelength laser operation at about 1 μm. The dual-wavelength Yb:YMB laser working at 1036 and 1062 nm with a maximum output power of 3.02 W and a slope efficiency of 46.9% was achieved, which may be a potential light source for THz generation with a large frequency difference of 7.1 THz. The results reveal that Yb:YMB is a promising multi-wavelength laser crystal.